Amdal in Implementing Safe Waste Management Practices in Menturus Village, Kudu District, Jombang Regency - Salisa Khoirun Salsabila; Abdur Rohman (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Tofu is a traditional dish crafted from processed soybeans. During the production of tofu, tofu by-products are generated. In Menturus village, there exists a tofu manufacturing facility, and this study aims to assess the effects of tofu by-product management and suggest improved management practices. A qualitative research method with a descriptive approach is used. Writing analysis is used to describe and interpret the current situation in qualitative descriptive research. These recommendations are then implemented through training for tofu business owners and continuous monitoring to evaluate the impact. The final report of this research highlights the findings and steps to promote responsible waste management practices in the tofu industry. Thus, this research not only provides an understanding of environmental impacts, but also encourages concrete actions to maintain environmental sustainability.